Making space for mutualism: urban common ground for human-wildlife coexistence - Qin, Yige (My University, 2022)
The natural environment and habitats around the city were disturbed due to urban growth, resulting in a reduction in biodiversity. Not only do humans migrate to cities to search for a better life, but certain wildlife also adjust their behavior and adapt to urban environments. City life provides "fast food" and shelter for wildlife, but due to the built environment and pressure from human activity, urban life is difficult for them. Urban wildlife could aid in the recovery and increase of urban biodiversity, providing numerous benefits such as aesthetic value and cures for mental health issues. However, there are human misunderstandings and concerns that wildlife brings disease, injury, and property damage. Making common ground for human-wildlife coexistence in the urban area is the topic of this thesis. The thesis aims to understand the relationship between the city, ecosystem, humans, and wildlife, as well as how they interact and influence one another, as well as to promote interaction and connection between humans and wildlife, and foster mutual trust. The research for design method was adopted. This thesis is built on the Social-ecological Urbanism theory and is guided by the principles of Landscape Ecology and the theory of Animal-Aided Design. The thesis analyzed the green network in Gothenburg´s central urban area to understand the ecological connectivity and how the green mosaic functions as a system. The red fox has been selected as the keystone animal, and to research the critical needs of the red fox and then analyze suitable locations from the red fox's perspective in Gothenburg´s central area. A series of essential sites for habitats were identified, followed by recommendations for rethinking and transformation to offer habitats for urban animals to survive and thrive and achieve the purpose. Urban green infrastructure is essential for urban wildlife to thrive. As a result, when we are in the position of urban planning, we should have a holistic and systematic view, understand how the green infrastructure functions as a system, and take the aspects of wildlife into consideration. The focus of the thesis is the process of exploring the problem, the application of theory to mapping and analysis, and the outcome of the thesis shows a strategic plan outlining the directions and suggestions for the transformation of the red fox's crucial places in central Gothenburg that supports their "urban life" and movement, allows human-wildlife interactions and coexistence, and contributes to the social-ecological outcome.